Stable Polymer Nanoparticles with Exceptionally High Drug Loading by Sequential Nanoprecipitation. (4th February 2020) - Liu, Yun; Yang, Guangze; Baby, Thejus; Tengjisi,; Chen, Dong; Weitz, David A.; Zhao, Chun‐Xia
Abstract: Poor solubility often leads to low drug efficacy. Encapsulation of water‐insoluble drugs in polymeric nanoparticles offers a solution. However, low drug loading remains a critical challenge. Now, a simple and robust sequential nanoprecipitation technology is used to produce stable drug‐core polymer‐shell nanoparticles with high drug loading (up to 58.5 %) from a wide range of polymers and drugs. This technology is based on tuning the precipitation time of drugs and polymers using a solvent system comprising multiple organic solvents, which allows the formation of drug nanoparticles first followed by immediate precipitation of one or two polymers. This technology offers a new strategy to manufacture polymeric nanoparticles with high drug loading having good long‐term stability and programmed release and opens a unique opportunity for drug delivery applications. Abstract : Ein einfacher Ansatz zur Nanofällung wird verwendet, um aus einer breiten Palette von Polymeren und Wirkstoffen Nanopartikel mit Medikamentenkern und Polymerhülle mit außergewöhnlich hoher Wirkstoffbeladung (bis zu 58.5 %) herzustellen. Diese Technik basiert auf der Abstimmung der Fällungszeit von Medikamenten und Polymeren mithilfe eines gemischten Lösungsmittelsystems.